Developing an Interactive Instructional Strategy Based on Arabic Vlog Media to Enhance Speaking Skills - Latifatul Baroroh; Nurul Hanani; Mohamad Anang Firdaus (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The mastery of Arabic speaking skills (Mahārah al-Kalām) is a critical competency in higher education, yet it is frequently hindered by passive, teacher-centered instructional methods and the resulting high levels of foreign language anxiety among students. While existing digital interventions like animated videos improve receptive skills, they often fail to stimulate productive communicative practice. This study aimed to develop, validate, and evaluate an interactive instructional strategy based on Arabic Video Blog (Vlog) media to actively engage students as content creators. Employing a Research and Development (R&D) design based on the ADDIE model, the study was conducted with fourth-semester students at Kiai Haji Abdul Wahab Hasbullah University. Data were gathered through expert validations, speaking tests, and student questionnaires. The results indicated that the vlog-based strategy achieved a